Polyaniline-MnFe2O4-CTAB Nanocomposite: Low Temperature Magnetic Investigation - Baykal, A.; Topkaya, R. (Springer, 2014)
Polyaniline-MnFe2O4 nanocomposite was successfully synthesized by using 1-butyl-3-methyl-imidazolium trifluoromethane sulfonate as room-temperature ionic liquid and cetyltrimethylammonium bromide (CTAB) as surfactant via in situ oxidative polymerization. The crystallite size of the product was calculated as 26 +/- 4 nm and cubic morphology was observed. The magnetic measurements reveal that the synthesized nanocomposite exhibited ferromagnetic behavior in the temperature range of 10-400 K. The nonsaturating magnetization behavior suggests the presence of disordered spins in surface layer. The lower saturation magnetization compared to bulk value results from the non-magnetic coating layer. The reduced remanent magnetization values lower than the theoretical value of 0.5 indicate the synthesized nanocomposite to have uniaxial anisotropy instead of cubic anisotropy according to the Stoner-Wohlfarth model.
Keywords: Oxidative polymerization; MnFe2O4; Room-temperature ionic liquids; Magnetic properties